Knowledge, Practice, and Associated Factors Towards Supplemental Oxygen Therapy Among Nurses Working in Neonatal Intensive Care Units in Public Hospitals of Addis Ababa, Ethiopia, 2022: A Cross-Sectional Study - Dansa A; Gela D; Kebede MA (Dove Medical Press, 2024)
Assefa Dansa,1 Debela Gela,2 Mekonen Adimasu Kebede2 1Department of Nursing, College of Health Sciences, Wolaita Sodo University, Wolaita Sodo, Ethiopia; 2Department of Nursing, School of Nursing and Midwifery, College of Health Sciences, Addis Ababa University, Addis Ababa, EthiopiaCorrespondence: Mekonen Adimasu Kebede, Department of Nursing, School of Nursing and midwifery, College of Health Sciences, Addis Ababa University, P O Box 0.1176, Addis Ababa, Ethiopia, Tel +2519-17724019, Email mekonen.adimasu@aau.edu.etPurpose: Proper administration of oxygen therapy for hospitalized newborns is undoubtedly essential. World Health Organization estimates that approximately 1.4 million deaths worldwide each year are due to inappropriate administration of oxygen, but its administration in clinical practice is usually inappropriate due to lack of knowledge and practice. Therefore, the aim of this study was to determine the level of knowledge, practice and associated factors related to supplemental oxygen therapy among nurses working in neonatal intensive care units.Methods: An institutional cross-sectional study was conducted with 166 randomly selected respondents using a self-administered questionnaire for data collection. Bivariate and multivariable analyses were performed using SPSS version 26. Variables with a p-value of < 0.25 in the bivariate analysis were included in the multivariable logistic regression, and statistical significance was ensured by a p-value < 0.05 with 95% CI.Results: One hundred and sixty-six nurses took part in this study, with a response rate of 96%. Of these, 60.8% had good knowledge and 54.2% had good practice in supplemental oxygen therapy. In the multivariable logistic regression analysis, work experience was significantly associated with knowledge (AOR: 5.40; 95% CI: 2.12- 13.73)) and practice (AOR = 3.69, 95% CI: 1.30- 10.44)) of supplemental oxygen therapy. Level of knowledge (AOR=2.92, 95% CI: (1.24- 6.86)) and educational status (AOR=6.51, 95% CI (1.34- 31.55)) were also significantly associated with the practice of supplemental oxygen therapy with a p < 0.05.Conclusion: Approximately 40% and 46% of nurses in this study had poor knowledge and practice of supplemental oxygen therapy. This figure is shocking and shows a large gap in the knowledge and practice of supplemental oxygen therapy that requires urgent action. Educational status, professional experience and level of knowledge were found to be associated with good knowledge and professional experience with good practice in relation to supplemental oxygen therapy.Keywords: knowledge, practice, neonatal nurse, oxygen therapy, neonatal intensive care unit